2012
DOI: 10.1002/mar.20566
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of In‐Store Greenery on Customers

Abstract: The incorporation of greenery in retail areas has scarcely been explored in environmental psychology studies. In a 2 × 2 experimental design, the effect of in‐store vegetation on consumer emotions and responses toward the store was studied, considering the moderating role of the information rate of the retail setting. While introducing foliage in the store environment did not evoke feelings of excitement, it was found to elicit pleasure and to reduce stress in a “complex” store interior. Given the impact of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 62 publications
(78 reference statements)
5
88
0
5
Order By: Relevance
“…Most of the studies focused on product displays and point-of-purchase information, as well as promotional signs, while neglecting greenery and other decoration factors like art works (Brengman, Willems, & Joye, 2012;Turley & Milliman, 2000). Yet, greenery might have a restorative effect on passengers, particularly those who are already experiencing strain from the journey to the airport or from an earlier flight, the check-in and security checks, etc.…”
Section: Point-of-purchase and Decoration Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies focused on product displays and point-of-purchase information, as well as promotional signs, while neglecting greenery and other decoration factors like art works (Brengman, Willems, & Joye, 2012;Turley & Milliman, 2000). Yet, greenery might have a restorative effect on passengers, particularly those who are already experiencing strain from the journey to the airport or from an earlier flight, the check-in and security checks, etc.…”
Section: Point-of-purchase and Decoration Factorsmentioning
confidence: 99%
“…(Joye, Willems, Brengman, & Wolf, 2010). Brengman et al (2012) recently reported evidence of the restorative effects of in-store vegetation. They found that foliage in a complex servicescape, but not in a lean servicescape (Bitner, 1992), elicited feelings of pleasure and reduced stress in passengers, and influenced their approach and avoidance behaviour in a favourable way.…”
Section: Point-of-purchase and Decoration Factorsmentioning
confidence: 99%
“…Maximization of the visitor's experience through environmental resources was suggested by Dewey (1922), who believed that there must be an interrelation between human beings and their environment. Specifically, the study of this variable or factor has a particular influence on consumer experience and behavior (Amérigo et al, 2013;Brengman et al, 2012;Do Paço and Raposo, 2009), which makes it a valuable resource in the Attraction factors of shopping centers field of commerce. Furthermore, the literature indicates that the design and composition of the ecological-commercial environment is an important research topic (Söderlund and Newman, 2015;Dover, 2015;Brengman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the commercial field, Brengman et al (2012) proved that the incorporation of spaces with vegetation impacts shopping behavior and emotions. Furthermore, the environmental design of commercial settings oriented toward the consumption and lifestyle in natural spaces favors the relation between the environment and their well-being (Amérigo et al, 2013;Herzog and Strevey, 2008).…”
Section: Identification Of Attraction Factors and Establishment Of Thmentioning
confidence: 99%
“…As the discussion about brick‐and‐mortar retailers versus online retailers intensifies (Turner, ), store managers rely on creative marketing initiatives to design socially pleasant store environments to attract traffic to their stores. Introducing in‐store vegetation (Brengman, Willems, & Joye, ), adopting thematic product displays (Lam, Ho‐ying Fu, & Li, ), using scents and fragrances (Fiore, Yah, & Yoh, ), and designing creative storefront window displays (Lange, Rosengren, & Blom, ), among others, are examples of such marketing initiatives/tactics. Yet, literature on the role of cues embedded in the front of the store (Turley & Milliman, ) is sparse and there is not much understanding about other factors that influence store image and store attachment (Cornelius, Natter, & Faure, ).…”
Section: Introductionmentioning
confidence: 99%